The DTA Curves for Melting of Hypereutectic AlSi Alloy - S. Wahab, M.; Ahmed, Aqeel; A. Raus, A.; Kamarudin, K.; Z. Radzi, E. (International Journal of Engineering and Technology, 2019)
Hypereutectic Al-Si alloy having Ëƒ12 wt% of Si, because of coarse and primary angular Si particles, it is very difficult to improve its mechanical, thermal properties and any phase change. Thermo Mechanical properties and phase change of material is completely depend on melting & solidification of material.Â  Differential thermal analysis is a relatively profound method for studying solidification and melting of alloys. It provides an exact estimation of the characteristic temperature of any phase changes with latent heat release or temperature variation. Such method is used here to a study the melting behavior of the Al-20Si and Al-25Si alloys with respect to temperature variation. Thermo gravimetric Analysis (TGA) resulted, the entire changes in mass of 1.57 mg and 1.43 mg for AlSi20 and AlSi25 alloys respectively. Differential Thermal Analysis (DTA) graph resulted the melting temperature of Al-20Si is 661 0C and for Al-25Si is 680 0C. These values are differing from the value of actual melting temperature of Al-Si alloy. The selection of heating rate is important to achieve better melting behavior results.Â Â